Clinicopathological Characteristics of Molecularly Classified Groups of Invasive Ductal Breast Carcinoma in Pakistani Women - Nausheen Henna; Faiza Shafqat; Manqoosh Ur Rehman; Shahzad Ahmed Fakhr; Sameer Anjum; Samra Sameen; Abdul Hannan Nagi (ziauddin University, 2024)
Background: The incidence of breast cancer warrants special consideration and understanding of disease demography. The study aimed to determine the clinicopathological characteristics of molecularly classified groups of invasive ductal breast carcinoma in Pakistani women. Methods: Patients (n=83) undergoing modified radical mastectomy with primary microscopically proven invasive ductal carcinoma were recruited from two tertiary care hospitals, Lahore, Pakistan. Grossing, reporting and biomarker testing was performed as per the College of American Pathologists (CAP) protocols. Chi-square was applied to observe associations between variables. A p-value <0.05 was considered statistically significant. Results: The mean age in years (mean ± SD) of the patients was 49.3 ±10.98, 50.9 ± 15.4, 50.6 ± 10.9 and 44.6 ± 8.2 having breast carcinoma of luminal A (37.2%), Luminal B (12%), HER2-enriched (20.5%) and triple-negative group (TN) (30.1%), respectively. Nodal involvement was 24(29%), 5(6%), 13(16%) and 17(20.5%) in all groups. Among four groups of breast carcinoma histological grade I was observed as 2.4%, 1.2%, 1.2%, 0%, grade II was recorded as 20.5%, 4.8%, 6 % and 7.2% and grade III as 14.5%, 6%, 13.3% and 22.9%, respectively. ​Luminal A patients were more in T2 stage whereas more TN patients belonged to T4 stage (p-value = 0.001). A statistically significant association was observed between T2 tumor stage with grade II (p-value = 0.003). Conclusion: Patients with Luminal A and triple-negative (TN) characteristics were the predominant molecular subtypes. TN patients presented at an earlier age and higher stage compared to other groups whereas, Luminal A profile patients were at the lower tumor stage. Keywords: Estrogen Nuclear Receptor; Mammary Ductal Carcinoma; Breast; Progesterone; Triple Negative Breast Cancer.​​​